Bi-axial flexural strength of resin based dental composites – Influence and reliability of the testing method configuration. (15th October 2022) - Kumar, Naresh; Ghani, Fazal; Fareed, Muhammad Amber; Riaz, Samiya; Khurshid, Zohaib; Zafar, Muhammad Sohail
ABSTRACT: This study aimed to determine the effect of the testing method configuration on the bi-axial flexural strength (BFS) of three resin-based dental composites (RDCs). A total of 180 disc-shaped samples (12 mm diameter x 1 mm thickness) for each RDC were fabricated using split back nylon mould. The BFS was determined for specimens made in three commercial RDCs; microhybrid (MH), nanofilled paste (NFP) and nanofilled flowable (NFF) using the ring-on-ring (RoR; n = 90 for each RDC specimens) and ball-on-ring (BoR; n = 90 for each RDC specimens) configurations at a cross-head speed of 1 mm/min. RDC specimens of MH and NFP tested in the BoR configuration showed higher mean BFS values compared to those tested in the RoR configuration. ( p < 0.001). The effect of test configuration on BFS values was insignificant for the specimens belonging to the NFF group ( p = 0.207). Moreover, the Weibull modulus of NFF in the RoR configuration was statistically lower compared to those for NFF in the BoR configuration as the 95% confidence interval of Weibull modulus did not overlap. The specimen support and testing configuration significantly impacted the BFS value of the RDCs. The Weibull statistics appeared to be inappropriate for all kinds of RDCs.